Legislation on oil pollution prevention and control during petroleum production - Md. Yassin, Abu Azam (Faculty of Chemical & Natural Resources Engineering, 1988)
Malaysia has long been a victim of oil pollution well before the start of her own offshore exploitation of oil. With the effort to exploit offshore oil and gas, Malaysia has now become a contributor to pollution. Legislation has already existed for oil pollution prevention and control, along each and every stage of offshore petroleum operations which include exploration, development, production, transportation, treatment and storage. But procedures to explain the existing legislation are lacking and hence it is important to expound the existing legislation for controlling and preventing oil pollution from offshore operation in line with current practices around the world.